2022
DOI: 10.3390/sym14030526
|View full text |Cite
|
Sign up to set email alerts
|

Insect Fluctuating Asymmetry: An Example in Bolivian Peridomestic Populations of Triatoma infestans (Klug, 1834) (Hemiptera: Reduviidae)

Abstract: Fluctuating asymmetry (FA) is a morphometric tool used to measure developmental instability in organisms which have been exposed to stress or other adverse conditions. Phenotypic variability in response to stressors are the result of interactions between genomes and the environment, acting in a noisy developmental system. Most of the organisms have bilateral symmetry with a repetition of structures in different positions or orientations; asymmetrical variation has been a morphological response associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Not many studies have evaluated fluctuating asymmetry in arthropods. Some of them currently use wing measurements to detect FA, but for this, they employ geometric morphometrics and area measurements (Benítez, 2013;Benítez et al, 2020;Vilaseca et al, 2022). In our study, since we measured apterous individuals, we obtained linear measurements of the traits.…”
Section: Discussionmentioning
confidence: 99%
“…Not many studies have evaluated fluctuating asymmetry in arthropods. Some of them currently use wing measurements to detect FA, but for this, they employ geometric morphometrics and area measurements (Benítez, 2013;Benítez et al, 2020;Vilaseca et al, 2022). In our study, since we measured apterous individuals, we obtained linear measurements of the traits.…”
Section: Discussionmentioning
confidence: 99%
“…This theoretical assumption is confirmed by studies which revealed that the presence and level of FA depend on larval host plants (higher FA on suboptimal/secondary host), for example, in Lepidoptera (Benítez et al., 2015) and Drosophila wings (Soto et al., 2008). Similarly, a recent study revealed that the combination of environmental characteristics (including feeding preference) changes levels of FA in wings in populations of the kissing bug Triatoma infestans (Klug) (Vilaseca et al., 2022). However, more data are needed to confirm the dependence between FA, stressful environments, and fitness (Cárcamo et al., 2008; Soto et al., 2010; Symanski & Redak, 2021).…”
Section: Introductionmentioning
confidence: 93%